Beta-catenin in the melanocyte lineage. - Larue, L; Kumasaka, M; Goding, C (2003)
beta-Catenin is a multifunctional protein involved in cell-cell adhesion, intracellular signalling and gene transcription. It has been implicated in the development of various lineages, including neural crest derivatives. Melanocytes are derived from neural crest cells and beta-catenin is expressed throughout the development of this cell lineage. The multifunctional activity of beta-catenin is directly associated with its participation in multi protein-protein interactions. The cell-cell adhesion function of beta-catenin is mediated by the large cadherin cell adhesion molecule family, the intracellular signalling function by its interaction with GSK3beta, and the gene transcription activity by the four known LEF/TCF DNA binding-proteins. Here, we review the known beta-catenin interacting factors and targets involved in the development and transformation of melanocytes and in particular its role in the expression of the crucial gene of melanocyte development, Mitf.